Electronic Cooling By Using Barium Titanate (Iv) Nanofluid With Loop Heat Pipe (lhp) - Tan, Aik Kwan (Universiti Sains Malaysia, 2019)
The reduction of size and the exponential increment in the number of integrated electronic components have eventually increased the power density and heat flux of the circuit. Barium titanate (IV) nanofluid has been proposed to replace the conventional cooling fluid such as water and ethylene glycol (EG). Barium titanate (IV) nanofluid is prepared at 0.1 vol.%, 0.3 vol.% and 0.5 vol.% with Arabic Gum (AG) as the surfactant. The thermophysical properties are studied with the nanofluid under heat output of 20 W, 40 W and 60W in a closed loop fluid system. The addition of barium titanate (IV) nanofluid is proven to improve the thermal conductivity by maximum of 31.28% compared to distilled water at 0.5 vol.%. However, in term of Nusselt number (Nu), distilled water shows superior heat transfer capability than nanofluids with maximum difference of 46.5% with nanofluids. Lesser heat is convected out than the heat is conducted into the RAM water block by nanofluid which causes fluid contact surface temperature to be greater than the results from distilled water. Hence, the combination of RAM water block and barium titanate (IV) nanofluid is not suitable for electronic cooling application.